Internet of Things (IoT)-Based Environmental Pollution Monitoring System - Satrio Rinaldo (Jurnal Jaringan Komputer dan Keamanan, 2024)
A healthy environment significantly benefits the well-being of living organisms, particularly humans. As intelligent and social beings, humans are obligated to conserve, maintain, and safeguard environmental cleanliness to ensure a healthy and clean habitat. For instance, the Palembang City Sanitation Office designates specific public waste disposal points where citizens should deposit their waste into provided receptacles, thereby preventing indiscriminate dumping that can lead to environmental damage or pollution. However, the existing waste collection process presents a challenge: sanitation officers often do not know when a garbage collection point is full. This lack of information results in foul odors, unsightly conditions, and residents discarding waste onto the roadside. This research, therefore, aims to develop an Internet of Things (IoT)-based system capable of automatically providing notifications and information about the garbage bin's fill level via an Android smartphone. The device is engineered to utilize an Ultrasonic sensor to provide input data to the ESP8266, which then relays the trash bin's capacity status (empty, half-full, or full). Testing of this environmental pollution monitoring tool, specifically for monitoring trash bin capacity, demonstrated the system's ability to automatically and periodically provide status notifications. This function was confirmed during the testing period from 07:00 to 16:00.